Sensing and analysis of spectrum holes in ISM band using USRP testbed - Nur Syahirah Binti Hamdan; Mas Haslinda Binti Mohamad; Aduwati Binti Sali (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
The spectrum frequency in the wireless communication industry is getting great attention due to the internet of things (IoT) technology's growth. However, the radio spectrum's frequency band use is limited because the primary user for specific services can cause spectrum interference as multiple users use the same spectrum frequency. Meanwhile, at each spectrum frequency, the number of users and utilization time are distinct. These will create vacancies for spectrum frequency assigned to the primary user. A new alternative in using the cognitive radio (CR) spectrum is accessible to these vacancies. This paper analyzed the frequency spectrum in the industrial, scientific and medical (ISM) band and identified spectrum holes for transmission by the secondary users. This work employed a realistic approach by measuring the spectrum using Universal Software Radio Peripheral (USRP) devices. Thus, the spectrum holes in the frequency spectrum had distinguished by using an energy detection technique. In the energy detection technique, the threshold energy level is set and then compared with the energy detector output to identify the primary user's existence (PU). The result indicates that 0.61% of spectrum holes have been detected in the 2.43-2.44 GHz range. This range is sufficient for home appliances, radio frequency peripherals (RF), and bluetooth devices.